Moisture content, density, and allometric model for estimating above-ground biomass of Peronema canescens trees in the private forest - KAMRAN KHAN; TOMY LISTYANTO; EMMA SORAYA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khan K, Listyanto T, Soraya E. 2022. Moisture content, density, and allometric model for estimating above-ground biomass of Peronema canescens trees in the private forest. Biodiversitas 23: 1132-1139. The objectives of this study were to quantitatively measure the above-ground biomass (AGB) of Peronema canescens Jack species in a private forest in Indonesia using a destructive method and to develop an allometric model for the same. Six trees were sampled for above-ground biomass and their components (stem, branch, and leaves) were weighted and measured. Regression analysis was used for developing the allometric equation by using predictor variables of diameter at breast height (DBH), squared diameter at breast height together with height (DBH2H), and diameter and height separately (D & H). The average AGB of six sampled trees was 0.264 (26.38%) tons per tree. The fit allometric equation AGB = 0.254(DBH2H)0.886 was developed for estimating above-ground biomass of P canescens and it had 99.2% accuracy. The implications and recommendations were provided based on the results of the study.